Time- and Zinc-Related Changes in Biomechanical Properties of Human Colorectal Cancer Cells Examined by Atomic Force Microscopy - Maares, Maria (Biology (Basel), 2020)
SIMPLE SUMMARY: We aimed to study how cellular zinc status (adequate vs. deficiency), closely related to colorectal cancer, does affect the nanomechanical properties of cell lines HT-29 and HT-29-MTX during their early proliferation (24–96 h). These properties and their variations can be characterized by means of Atomic Force Microscopy (AFM), a technique that allows perpendicular indentation of cells with a sharp nanometric tip, under controlled speed and load, while recording the real time variation of tip-to-cell interacting forces on approach, contact, and retraction segments. From each of these sections, complete information about the respective elastic modulus, relaxation behavior, and adhesion is extracted, thus identifying cell line- and zinc-related nanomechanical fingerprints. Our results show how the impact of zinc deficiency on the mechanical response of the cells underlines the relevance of monitoring the nutritional zinc status of tumor samples when analyzing cancerous tissues or single cells with AFM, particularly regarding the development and validation of biomechanical fingerprints as diagnostic markers for cancer. ABSTRACT: Monitoring biomechanics of cells or tissue biopsies employing atomic force microscopy (AFM) offers great potential to identify diagnostic biomarkers for diseases, such as colorectal cancer (CRC). Data on the mechanical properties of CRC cells, however, are still scarce. There is strong evidence that the individual zinc status is related to CRC risk. Thus, this study investigates the impact of differing zinc supply on the mechanical response of the in vitro CRC cell lines HT-29 and HT-29-MTX during their early proliferation (24–96 h) by measuring elastic modulus, relaxation behavior, and adhesion factors using AFM. The differing zinc supply severely altered the proliferation of these cells and markedly affected their mechanical properties. Accordingly, zinc deficiency led to softer cells, quantitatively described by 20–30% lower Young’s modulus, which was also reflected by relevant changes in adhesion and rupture event distribution compared to those measured for the respective zinc-adequate cultured cells. These results demonstrate that the nutritional zinc supply severely affects the nanomechanical response of CRC cell lines and highlights the relevance of monitoring the zinc content of cancerous cells or biopsies when studying their biomechanics with AFM in the future.